Influencing Parameter Study on Primary Breakup of Free Falling Steel Melt Jets Using Volume of Fluid Simulation. Issue 8 (25th May 2016) - Neumann, Sebastian; Dubberstein, Tobias; Chaves, Humberto; Kirmse, Clemens; Schwarze, Rüdiger
Abstract : The free falling liquid steel jet behavior is numerically investigated using implicit large eddy simulations (ILES) and the volume of fluid (VOF) approach. The research is focused on primary breakup phenomena near the nozzle using the standard open‐source computational fluid dynamics library OpenFOAM. To quantify the influence of process and constructional parameters exclusively for the structure of a free falling liquid steel jet, several central conditions are explored. The calculations concentrate on disturbances at the nozzle inlet due to adverse inflow conditions. The jet behavior is caused by an asymmetrical lift of the stopper rod and a liquid steel rotation in the tundish based on the magnetic heating process, which is transported into the nozzle due to the conservation of angular momentum. The calculations with adjusted rotation show distinct influences with developing structures like helix or hollow‐cone‐shaped jets. Differences are observed based on the nozzle type. In particular, a tube nozzle (constant diameter) and an industrial nozzle setup (divergent–convergent shape) are investigated. The inflow conditions have a large influence on the tube nozzle, where the outflow is delayed and the jet disintegrates. However, the industrial nozzle type shows less impact, but the jet surface is in general more corrugated and disturbed. Abstract : The free falling liquid steel jet behavior is numerically investigated using implicit large eddy simulations and the volume of fluid approach. The research focuses on primary breakup phenomena near the nozzle, quantifying the influence of process and constructional parameters. The jet behavior shows distinct inflow and nozzle design dependencies, which influence the jet shape and disintegration into ligaments or droplets.